Islamic Da'wah Challenge in Marriage of Different Religions in a Contextual Interpretation Review - Safrodin Safrodin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2022)
This paper aims to explain the opportunities and challenges of Islamic da'wah in interfaith marriages between Muslim men and Ahl al-Kitab women from the point of view of the interpretation of the Qur'an. The research is directed to explore the perspective of da'wah in answering polemics about interfaith marriages. The study method in this paper is a qualitative study with the muqaran (contextual) interpretation method. The results of this study explain that it is permissible for Muslim men to marry Ahlu Kitab women (as stated in al-Maidah: 5) as an opportunity for preaching and preaching among non-Muslims in addition to challenges. This da'wah opportunity can be seen in the existence of a patriarchal social system, where the husband has a substantial, more dominant role as the leader of the family, making it possible to convey enlightenment about Islam in a dialogical, humanistic, mauidzah hasanah and promising way to his wife so that she can know the truth of Islam, understand it to the fullest. Believe it. Meanwhile, the challenge Muslim husbands face in da'wah is the necessity of having strong faith in addition to good da'wah competence so that, on the one hand, he does not waver in his faith and his da'wah efforts also do not disturb the harmony of his relationship with his wife. The results of this study provide space for da'wah to non-Muslims through interfaith marriages for competent Muslim men.